2018
DOI: 10.1590/1806-9282.64.09.824
|View full text |Cite
|
Sign up to set email alerts
|

Home-based exercise therapy for treating non-specific chronic low back pain

Abstract: SUMMARY OBJECTIVE To evaluate pain, functional capacity, and quality of life of patients with non-specific chronic low back pain, after home-based exercise therapy with different kinds of supervision. METHOD Thirty individuals of both gender, between 18 and 65 years old, performed the proposed exercises three times a week, for eight weeks. Group A (N = 17) performed the exercises after a single supervised session. Group B (N = 13) was supervised once a week at the rehabilitation center. Both groups receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(56 citation statements)
references
References 16 publications
3
51
0
2
Order By: Relevance
“…8 Home exercise programme showed to be effective in treatment of chronic low back pain, but there was low adherence to and improper application of exercises. 6,9 All of these are available in numerous smartphone applications educating patients for self-management of low back pain. However, these applications were not developed by professionals, not based on scientific evidence, and/or their effectiveness was not established.…”
Section: Introductionmentioning
confidence: 99%
“…8 Home exercise programme showed to be effective in treatment of chronic low back pain, but there was low adherence to and improper application of exercises. 6,9 All of these are available in numerous smartphone applications educating patients for self-management of low back pain. However, these applications were not developed by professionals, not based on scientific evidence, and/or their effectiveness was not established.…”
Section: Introductionmentioning
confidence: 99%
“…An important concern about home physical exercise programs is related to patient adherence without supervision. Kanas et al 34 evaluated home exercises in patients with chronic low back pain for a period of eight weeks, comparing two groups, with and without the supervision of a health professional, but with the help of a booklet, and concluded that the latter was effective for pain improvement, functional capacity and quality of life. The supervision did not significantly influence the final result when comparing the groups 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Kanas et al 34 evaluated home exercises in patients with chronic low back pain for a period of eight weeks, comparing two groups, with and without the supervision of a health professional, but with the help of a booklet, and concluded that the latter was effective for pain improvement, functional capacity and quality of life. The supervision did not significantly influence the final result when comparing the groups 34 . These data corroborate the present study; even with the patients not being personally supervised, they had good adherence to the program and, with the completion of an exercise diary, it was possible to follow the evolution of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence reports that home-based exercise therapy, when performed has been found to be effective for improving level of pain, functional capacity, and quality of life in patients with non-specific chronic low back pain [2]. Rehabilitation services by use of digital technology is cost effective, helps to maintain continuity of care, educate patients through remote consultation, also allows for performing a physical assessment, plan a targeted therapeutic exercise program, and monitor patients' progress, providing them continuous supervision and feedback.…”
mentioning
confidence: 99%
“…Use of mobile-app platform of the McKenzie extension protocol has comparable clinical outcomes with the traditional clinic-based McKenzie therapy, and thus an effective supplementary platform for care of patients with low-back pain [ 4 ]. Thus, preliminary evidence suggests adopting tele-rehabilitation in substitute of face-to-face physical rehabilitation for improving pain scores and quality of life in patients affected by back pain [ 2 - 4 ].…”
mentioning
confidence: 99%